Transcoronary concentration gradient of sCD40L and hsCRP in patients with coronary heart disease - Wang, Ying; Li, Li; Tan, Hong‐Wei; Yu, Guang‐Sheng; Ma, Zhi‐Yong; Zhao, Yu Xia; Zhang, Yun (Clinical cardiology (Mahwah, N.J.), 2007)
Background Recent studies indicated that local inflammation played a pivotal role in the pathogenesis of coronary heart disease. Soluble CD40 ligand (sCD40L) and hsC‐ reactive protein (hsCRP) are important inflammatory mediators. However, whether they can reflect local coronary inflammation is unclear. Hypothesis We hypothesized that transcoronary concentration gradient of sCD40L could reflect local inflammation in patients with coronary heart disease (CHD) more reliably. Methods Forty subjects were divided into unstable angina pectoris (UAP) group (n = 20), stable angina pectoris (SAP) group (n = 10), and controls (n = 10). Blood samples were collected from the coronary sinus (CS), aortic root (AO), and femoral vein (FV). The coronary circulation was expressed as CS‐AO difference, while system circulation was expressed as FV‐AO difference. sCD40L and hs‐CRP were measured. Results Complex lesions were more frequent in the UAP group than in the SAP group (85% vs. 40%, p < 0.05). CS‐AO differences of sCD40L were much greater in the UAP group than in the SAP or control groups, and were greatly higher than FV‐AO difference in UAP group (465.49 ± 247.85 pg/mL vs. −14.94 ± 83.41 pg/mL; 465.49 ± 247.85 pg/mL vs. −7.66 ± 78.54 pg/mL; 465.49 ± 247.85 pg/mL vs. −7.99 ± 141.34 pg/mL, all p < 0.001). CS‐AO differences of sCD40L were higher in patients with complex lesions than with smooth lesions (657.86 ± 384.76 pg/mL vs. 317.62 ± 409.98 pg/mL, p < 0.01). There were no significant differences of CS‐AO in hs‐CRP among the three groups. Conclusions In patients with CHD, the transcoronary concentration gradient of sCD40L is more sensitive than hsCRP, and sCD40L possibly a better marker of local inflammtion and plaque instability. Copyright © 2007 Wiley Periodicals, Inc.